Extension on Efforts to Increase the Quality of Gumantar Coffee Through Improved Harvest and Post-Harvest Techniques - Pandya, Lalu Wahyu Ardis; Prisetyatna, Sibyanula; Apriani, Nia; Yuliastri, Baiq Nova; Ramadhan, M. Raka; Oktaviani, Salsabila; Yuniarti, Eva; Wulandari, Fitri; Anindy, Reinasha Cahya; Cahyani, Nanda Meilina; Badrun, Liana Suryaningsih; Jaya, I Komang Damar (Pascasarjana Universitas Mataram, 2024)
The quality of coffee, including taste and aroma, is determined mainly by the timeliness of harvesting and post-harvest processes. The quality of Robusta coffee produced in Tenggorong Hamlet, Gumantar Village, North Lombok Regency is still relatively low because the harvesting of coffee beans is carried out using the strip picking method and not the selective picking method. The post-harvest method is still inappropriate, especially in the section for producing green beans. This extension aimed to improve the quality of Gumantar Village coffee through activities to increase farmers' knowledge and capacity in conducting harvest and post-harvest processes. Marketing facilitation activities were also carried out using various applicable process standards. The results and evaluation of the activities showed an increase in coffee farmers' knowledge and capacity in selective picking and post-harvest coffee processing. Coffee processing methods that determine the taste, such as green bean preparation and roasting, have also been well understood. The facilitation has resulted in a business identification number (NIB), label and packaging logo with 'Sangakopi' product brand rights, halal certificate, and distribution permit. It is expected that 'Sangakopi' products will enter the NTB Mall shortly.